Impact of obesity on the severity of trauma in patients injured in pedestrian traffic accidents - Pillsung Oh; Jin-Seong Cho; Jae Ho Jang; Jae Yeon Choi; Woo Sung Choi; Byungchul Yu (Journal of Trauma and Injury)
Purpose Studies on the relationship between obesity and injuries, especially those sustained in pedestrian traffic accidents, are lacking. We aimed to assess the effects of obesity on the severity of injury at the time of admission to the emergency room in patients who experienced pedestrian traffic accidents. Methods This study included trauma patients registered in the Korean Trauma Database from July 1, 2018 to December 31, 2020, whose mechanism of injury was pedestrian traffic accidents and who were treated at a single institution. Those aged below 15 years were excluded. Patients were assigned to nonobese and obese groups based on a body mass index of 25 kg/m2. An Injury Severity Score of 25 or greater was considered to indicate a critical injury. Results In total, 679 cases of pedestrian traffic accidents were registered during the study period, and 543 patients were included in the final analysis. Of them, 360 patients (66.3%) and 183 patients (33.7%) were categorized as nonobese and obese, respectively. The median age was significantly higher in the nonobese group than in the obese group (60 vs. 58 years). Multivariate analysis demonstrated that the odds ratio for critical injury in obese patients was 1.59 (95% confidence interval, 1.01–2.48) compared with nonobese patients. Conclusions Obesity affected the likelihood of sustaining severe injuries in pedestrian traffic accidents. Future studies should analyze the effects of body mass index on the pattern and severity of injuries in patients with more diverse injury mechanisms using large-scale data.